2011
DOI: 10.1016/j.funeco.2010.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tree species on richness and diversity of epigeous fungal communities in a French temperate forest stand

Abstract: Epigeous saprotrophic and ectomycorrhizal (ECM) fungal sporocarps were assessed during 7 yr in a French temperate experimental forest site with six 30-year-old mono-specific plantations (four coniferous and two hardwood plantations) and one 150-year-old native mixed deciduous forest. A total of 331 fungal species were identified. Half of the fungal species were ECM, but this proportion varied slightly by forest composition. The replacement of the native forest by mono-specific plantations, including native spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 41 publications
4
59
1
Order By: Relevance
“…Facilitation mechanisms such as hydraulic lift whereby deeper rooting tree species take up water and redistribute it via their root system to drier superficial soil layers are also known to take place in mixed forest ecosystems (18). Higher functional diversity of the fungal community could also partially improve water availability in more diverse stands (19). These underlying processes nevertheless remain speculative and future research is needed to shed light on the relative contribution of these potential processes (20).…”
Section: Discussionmentioning
confidence: 99%
“…Facilitation mechanisms such as hydraulic lift whereby deeper rooting tree species take up water and redistribute it via their root system to drier superficial soil layers are also known to take place in mixed forest ecosystems (18). Higher functional diversity of the fungal community could also partially improve water availability in more diverse stands (19). These underlying processes nevertheless remain speculative and future research is needed to shed light on the relative contribution of these potential processes (20).…”
Section: Discussionmentioning
confidence: 99%
“…Ectomycorrhizal species belonging to Inocybe and Lactarius are fairly common in various plant communities [43] and in environments in which truffles are produced [44,45]. Thelephoraceae species are common morphotypes on root tips in boreal forests [45] and in environments of truffle production [16,[34][35][36]39,41,47].…”
Section: Discussionmentioning
confidence: 99%
“…This result is surprising since usually the number of fungal species in plantations increases with time [43,52]. This may be due to the plantation management.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, multivariate statistics have shown that macrofungal communities can be clearly defined and delineated from the abundance patterns of their host tree species in temperate forests (Humphrey et al 2000, Ferris et al 2000, Buée et al 2011, O'Hanlon & Harrington 2012. In this study, EMF were associated with woody plants, including not only trees but also aged shrubs (taller than 2m).…”
Section: Discussionmentioning
confidence: 99%